Adjusting hydrophilicity of g-C3N4 based heterojunction photocatalyst through sulfur-impregnation to enhancing degradation effect of tetracycline. (May 2023) - Kang, Shirong; Zhu, Hongjie; Wang, Linhua; Zhao, Xiaoyan; Huang, Xianqiang; Yang, Hua; Dou, Mingyu; Li, Dacheng; Dou, Jianmin
Abstract: Tetracycline, a class of micropollutants, is pharmaceutically active compound which cannot be disintegrated borrowing routine treatment methods. Herein, the nano-heterostructures with strong hydrophilicity were obtained via the intervention from acetonitrile and methanol double solvent system at the room temperature. Specifically, the hydrophilic sulfur-impregnated g-C3 N4 coupled with 1 dimensional CeO2 were designed for enhancing dispersity and photocatalytic activity, the results of optical properties demonstrated sulfur-impregnated samples and composites expressed the low recombination of photogenerated carriers compared to the pristine material in that the newborn N–S bonding, which was confirmed via the density functional theory computation and X-ray photoelectron spectroscopy. In this work, the impregnation strategy adopted amplified the hydrophilicity of the material, which had reference significance for the study of hydrophilic and hydrophobic regulation of nanomaterials. Besides, the photodegradation mechanism and pathway of TC was investigated via the results of radical quenching experiment and mass spectrometry analysis, respectively. This study provided a reference for the fertilization modification of intrinsic semiconductor materials under the mixed solvent system and it was contributed to the photodegradation study of TC similarly. Graphical abstract: Image 1 Highlights: Hydrophilic catalysts synthesis via double solvent system containing acetonitrile. Construction of hydrophilic nano-heterostructures for TC degradation. Intermediates and possible degradation pathway were inferred on TC during photodegradation process.